JAMINAN PRODUK HALAL DALAM UNDANG-UNDANG NO. 33 TAHUN 2014 DALAM TINJAUAN MAQASHID - Lu’lu’ Nishfu Laili; Misno (Institut Agama Islam Sahid Bogor, 2023)
This journal analyzes maqashid concerning halal product guarantees according to Law No. 33 of 2014. This journal analysis focuses on the concept of halal product guarantees according to Islamic law and the conformity of Law No. 33 of 2014 concerning Guarantees of Halal Products with Maqashid Syariah. The research method used by the author is normative juridical research with a qualitative descriptive type. The research concludes that this law is compatible with Maqashid Syariah.